Symptomatic Sinus Bradycardia in a Patient with Acute Calculous Cholecystitis Due to the Cardio-Biliary Reflex (Cope’s Sign): A Case Report - Tutul Chowdhury (A Case in a Million, 2023)
Acute cholecystitis may present cardiovascular manifestation like cardiac ischemia leading to detailed cardiac workup without any obvious cardiac pathology. Here we describe a case who presented with typical signs and symptoms of cholecystitis exhibiting sinus bradycardia. This reflexive bradycardia was a result of autonomic vagal innervation and was resolved after cholecystectomy. This case highlights the importance of the cardio-biliary reflex and recommends clinicians ensure expedited management of cholecystitis to avoid unnecessary extensive cardiac workup.